IDMILE: An interactive didactic math inclusion learning environment for blind students. - Jitngernmadan, Prajaks; Stöger, Bernhard; Petz, Andrea; Miesenberger, Klaus (Technology & Disability, 2017)
The preparation of mathematical learning content for blind students does not include many elements of the implicit didactic information included in the visual layout of math schoolbooks, e.g. spatial arrangements for sequencing or relations, color-coded information, and other layout based content representation. This kind of information is an indispensable component for up-to-date math learning and teaching. Due to the limitation of other senses and assistive devices for blind people, this missing of explicit semantic mark-up of these implicit didactical elements is seen as one key reason for the disadvantages of in STEM education and related job opportunities. This paper presents basic research on developing an approach for making this implicit information accessible by marking-up the implicit visual elements used in math schoolbooks, which goes beyond linear text. Describing and marking-up this dynamic content forms the base for our prototyping of an inclusive math-learning environment for blind students. Interactive dialogues guide the blind user and provide assistive functionalities for better managing the complexity when solving math problems using sequential audio, refreshable braille display, and other presentation and interaction methods. In this attempt, our prototype covers four basic arithmetic operations. We use the Eclipse SWT framework and Microsoft UI Automation to be in line with known accessibility concepts and skills of users. The prototypes have been evaluated both by blind and sighted persons.